Why our ancestors never invented telescopes - Mokgoatšana, Sekgothe (HTS teologiese studies, 2020)
The Afrikaner civil rights organisation AfriForum argued, following a parliamentary adoption of land expropriation without compensation, that there is no history of Native South Africans having occupied every inch of the country that they now claim they want to repossess. The organisation’s representatives argued that by their very subsistence agrarian existence, black people could not have lived in the platteland because their farming methods demanded access to rivers to water their crops. In the 1950s – 1970s, thousands of communities were uprooted in and around Pilgrim’s Rest (Mpumalanga) and relocated to derelict parts of the homeland of Lebowa. Since the opening of the land restitution process, they have struggled to reclaim that arable land of which they were dispossessed for the benefit of Barloworld and Transvaal Gold Mining Exploration. A settlement has been reached with the claimants, and the land has been entrusted to Community Property Associations (CPA). However, there are contested memories about what constituted a forced removal and who qualifies to claim land in the repossessed spaces. The reclaiming of the vast tracts of land, some of which lie far from rivers, is answering some of the questions that form part of the current national discourse.Contribution: This article continues the controversial debate of land claims, and the impact they have on communities. Unlike other studies that explore economic impacts, this article puts a spotlight on how dispossession not only uproots communities but destroys their livelihood and indigenous resources for food security, healthcare and traditional resources for medical practice.